The Impact of P2P Lending on Commercial Bank's Market Share: Bank-Level Evidence - Tran, Thi Xuan Anh; Nguyen, Le Thu (Riset Akuntansi dan Keuangan Indonesia, 2025)
This study offers the first thorough analysis of how Peer-to-Peer (P2P) lending has affected the market share of commercial banks in Vietnam. It does so with a special emphasis on shareholder characteristics, such as the proportion of foreign and state-owned shares. The study, which examined data from 31 commercial banks between 2017 and 2023, found that, whereas marketplace lending has a beneficial effect on conventional banks' market share, P2P has a negative impact on banks' market share. Notably, this is the first study to show that state-owned banks often hold a bigger market share than banks with a larger foreign owner structure when it comes to peer-to-peer lending. Moreover, this study is the first to pinpoint how market discipline helps lessen the negative impact of peer-to-peer lending on the market share of commercial banks. In light of the emergence of peer-to-peer lending platforms, these insights are essential for investors, commercial banks, and legislators to effectively navigate the changing peer-to-peer lending landscape, plan ahead, and maintain the stability and competitiveness of the banking sector. This study pushes traditional banks to capitalize on the rapid advancement of technology to improve client experiences and market share, and it also broadens the conversation about the relationship between traditional banking and developing financial innovations.